The development of a culturally appropriate school based intervention for Australian Aboriginal children living in remote communities: A formative evaluation of the Alert Program® intervention. (13th December 2016) - Wagner, Bree; Fitzpatrick, James; Symons, Martyn; Jirikowic, Tracy; Cross, Donna; Latimer, Jane
Abstract : Background/aim: Although previous research has demonstrated the benefits of targeting self‐regulation in non‐Aboriginal children, it is unclear whether such programs would be effective for Aboriginal children attending school in remote communities. Some of these children have been diagnosed with a fetal alcohol spectrum disorder (FASD) impairing their ability to self‐regulate. The aim of this article is to describe a three phase formative process to develop and pilot a curriculum version of the Alert Program ®, a promising intervention for improving self‐regulation that could be used in remote community schools. This modified version of the program will be subsequently tested in a cluster randomised controlled trial. Methods: A mixed methods approach was used. Results: Modifications to the Alert Program ®, its delivery and evaluation were made after community and stakeholder consultation facilitated by a senior Aboriginal community researcher. Changes to lesson plans and program resources were made to reflect the remote community context, classroom environment and the challenging behaviours of children. Standardised study outcome measures were modified by removing several questions that had little relevance to the lives of children in remote communities. Program training for school staff was reduced in length to reduce staff burden. Conclusions: This study identified aspects of the Alert Program ® training, delivery and measures for evaluation that need modification before their use in assessing the efficacy of the Alert Program ® in remote Aboriginal community primary schools.